2021
DOI: 10.1016/j.sjbs.2021.06.088
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA PLOD2 enhances ovarian cancer propagation by controlling miR-378

Abstract: It has been confirmed that circular RNA participates in tumorgenesis through a variety of ways, so it may be used as a molecular marker for tumor diagnosis and treatment. In this study, the expression of circ-LOPD2 in ovarian cancer tissues and cell lines was detected by qRT-PCR and Western blot. The dual luciferase report was used to verify the target of circ-LOPD2, and the silencing and overexpression of circ-CSPP1 in cell lines was used to explore its relationship with miRNA-378. The cell proliferation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…We first looked at potential miRNA involvement. However, contrary to a previous report 17 , we observed neither a generally increased density of miRNA target sites nor an enrichment for any particular miRNA ( Figure S3B ). Moreover, in publicly available AGO2 pulldown data 18 , we only found two peaks of AGO2 binding in circPLOD2, presumably harboring two miRNAs, however, their predicted targets showed no directed regulation in circPLOD2-depleted pericytes ( Figure S3C ).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…We first looked at potential miRNA involvement. However, contrary to a previous report 17 , we observed neither a generally increased density of miRNA target sites nor an enrichment for any particular miRNA ( Figure S3B ). Moreover, in publicly available AGO2 pulldown data 18 , we only found two peaks of AGO2 binding in circPLOD2, presumably harboring two miRNAs, however, their predicted targets showed no directed regulation in circPLOD2-depleted pericytes ( Figure S3C ).…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, in publicly available AGO2 pulldown data 18 , we only found two peaks of AGO2 binding in circPLOD2, presumably harboring two miRNAs, however, their predicted targets showed no directed regulation in circPLOD2-depleted pericytes ( Figure S3C ). Finally, target sites of the previously described circPLOD2-interacting miRNA miR-378 17 were neither predicted nor detected in the AGO2 pulldowns. Based on these observations, we concluded that circPLOD2 most likely does not interfere with miRNA regulation.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…circ-LOPD2 expression is high in both OC tissue and cells and is responsible for promoting OC cell proliferation. 63 Several studies have revealed that circ-RNAs worked as molecule sponges of miR-378a to regulate cancer development.…”
Section: Upregulation Of Mir-378a Promotes Malignant Transformation A...mentioning
confidence: 99%
“…Ovarian cancer (OC) is the second leading cause of mortality among women with gynaecological cancers worldwide. 74 Previous research has discovered that NTN1 is overexpressed in the vast majority of malignant ovarian tumours but not in benign tumours. Moreover, the correlation between high NTN1 expression and tumour stage and grade suggests that NTN1 may perform an oncogene role in OC.…”
Section: Ovarian Cancermentioning
confidence: 99%